2020
DOI: 10.1002/jmv.26271
|View full text |Cite
|
Sign up to set email alerts
|

HIV and SARS CoV‐2 coinfection: A retrospective, record‐based, case series from South India

Abstract: HIV prevalence in India is about 0.22%, with the total number of people living with HIV/AIDS (PLHA) is estimated at 21.40 lakhs, constituting third largest epidemic in world. However, no study on HIV‐COVID‐19 co‐infection has been reported from India. We conducted a retrospective, record based case series including three males, 2 females and 1 transgender PLHA co‐infected with SARS CoV‐2 in the Indian state of Tamil Nadu. Fever (5), followed by cough (2) and sore throat (1), were the presenting symptoms. Lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 9 publications
2
26
0
1
Order By: Relevance
“…In some cohort studies, HIV-infected persons hospitalized for COVID-19 had similar clinical characteristics and outcomes with other hospitalized cohorts of HIV-uninfected patients, and risk of COVID-19 and severe disease in suppressed HIV-positive people seems to be comparable with the general population. 6 16 Particularly, a recent systematic review suggests that patients with controlled HIV infection (or rather with CD4 + lymphocyte count >200 cells/mm 3 and undetectable viral load) have the same risk of contracting SARS-CoV-2 infection or experiencing more severe COVID-19 in comparison with HIV-uninfected people. 17 …”
mentioning
confidence: 99%
“…In some cohort studies, HIV-infected persons hospitalized for COVID-19 had similar clinical characteristics and outcomes with other hospitalized cohorts of HIV-uninfected patients, and risk of COVID-19 and severe disease in suppressed HIV-positive people seems to be comparable with the general population. 6 16 Particularly, a recent systematic review suggests that patients with controlled HIV infection (or rather with CD4 + lymphocyte count >200 cells/mm 3 and undetectable viral load) have the same risk of contracting SARS-CoV-2 infection or experiencing more severe COVID-19 in comparison with HIV-uninfected people. 17 …”
mentioning
confidence: 99%
“…There are rapidly growing information on COVID-19 infection, however, the data in HIV population remains contradictory [7,8]. Previous studies observed that low CD4 + T cell counts could actually protect against severe form of COVID-19, which suggested that immune system activation may actually increase the injury caused by COVID-19 and low CD4 + T cell counts might protect HIV-positive individuals from developing the cytokine storm observed in patients with COVID-19 [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The current COVID-19 treatment guidelines issued by the NIH recommend against the use of lopinavir/ritonavir protease inhibitors (AIII) for the treatment of COVID-19, and is restricted to clinical trials. 18,19 Various large clinical case series have corroborated the growing evidence that patients with HIV/SARS-CoV-2 co-infection do not have excess morbidity and mortality when compared to non-HIV COVID-19…”
mentioning
confidence: 92%